Evaluation of Women’s Satisfaction Regarding MCH Services Provided in Health Care Centers with High Maternal and Infant Mortality Rate in Wassit Governorate - Thani Sadoon , Ahmed; Hussein Bahir, Basim (Diyala Journal of Medicine, 2020)
Background: As client opinion is useful to improve MCH service delivery, evaluation of client satisfaction should be undertaken periodically. Objective: To determine the level of satisfaction of pregnant women and mothers regard health care services provided in the MCH units in Wassit Governorate. Patients and Methods: A cross-sectional study, with a convenient sample of mothers and pregnant women who were attending to the MCH clinics. The study was conducted in three sectors with high maternal and infant mortality rate which include 28 health care centers in Wassit Governorate. Data were collected through the period starting on 16 December 2018 and ending on 31 March 2019, using a specially designed questionnaire. Results: The important inference of this study is the quality of care from the pregnant women and mothers perspective that reflected in client satisfaction. This study has revealed that (67.5%) of pregnant women were fairly satisfied, while 67.1% of mothers were fairly satisfied with health care services provided in MCH units at different PHC centers in Wassit city. Conclusion: This study revealed that the majority of pregnant women and mothers were fairly satisfied with health care services provided by the MCH unit in the Wassit Governorate and the quality of antenatal care and care for children less than 5 years provided at studied MCH centers need to be improved in all activities.